The identification of skills and competencies for effective management in social enterprises. A managerial perspective = Cechy i kompetencje w zarządzaniu przedsiębiorstwem społecznym. Perspektywa menedżerska - Wronka-Pośpiech, Martyna (Zielona Góra: Faculty of Economics and Management Press)
The need to adapt to external business requirements, turbulences present in the environment as well as the dynamic changes occurring in the non-profit sector require the presence of managers who are not only capable of taking proper care of financial issues, but also of optimally deploying available human resources.
Keywords: przedsiębiorczość społeczna; zarządzający przedsiębiorstwem społecznym; kompetencje; przywództwo; przedsiębiorstwo społeczne; ekonomia społeczna; social entrepreneurship; social enterprise manager; competencies; social economy; social enterprise; leadership